NEW CHALLENGES FOR TEACHERS WORKING IN EARLY CHILDHOOD EDUCATION - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2022)
This article considers perceptions of children’s learning and classroom practice to support learning in Uzbekistan early years educational context. In Uzbekistan , there is a growing focus on quality provision of early childhood education and building early childhood education teacher capacity. Over the course of one academic year, data were collected from kindergarten teachers in an urban school through interviews and classroom observations as part of a larger study. The perceptions of kindergarten children’s learning and of their practice to support kindergarten children’s learning, taking into consideration the gender perspective. The results showed tensions in the teachers’ perceptions which contrasted between a constructivist approach and a teacher-directed skills approach. Perceptions of their practice reflected a formal, teacher-directed approach rather than a constructivist approach and a teacher-directed skills approach to teaching. Several factors, including deep-rooted perceptions as well as curriculum structure, time, number of staff and resources, contributed to this.